Mutations in apoptosis-related gene, PDCD10, cause cerebral cavernous malformation 3 - (:unkn) unknown (OXFORD UNIV PRESS INC, 2005)
OBJECTIVE: To identify the CCM3 gene in a population of 61 families with a positive family history of cerebral cavernous malformations (CCM), 8 of which had suggestive linkage to the CCM3 locus. METHODS: We searched for mutations within the CCM3 interval using a high-throughput screening technique, temperature-gradient capillary electrophoresis. Mutations detected by this device were subsequently sequenced, and the results were analyzed. RESULTS: A recent study by Bergametti et al. established Programmed Cell Death 10 (PDCD10) as the gene responsible for CCM3. We hereby confirm PDCD10 as the CCM3 gene by reporting four novel mutations in 61 CCM families. Two of these mutations were identical and produced a stop codon in exon 7. Another two resulted in frameshift mutations in exon 6, although the mutations occurred at different points along the exon. The last mutation caused a frameshift in exon 9. Of note, mutations in these families completely cosegregated with the trait. Three of the five families had prior linkage data suggestive of the CCM3 locus, whereas the remaining two were identified in index patients with a positive family history but no linkage data. CONCLUSION: Our data establish PDCD10 as the gene responsible for CCM in families linking to the CCM3 locus. The discovery of the third gene involved in inherited forms of CCM, after KRIT1 and Malcavrnin, is an important step toward dissecting the molecular pathophysiology of this disease.
Keywords: CCM3; familial cavernous malformations; genetics; mutations in CCM3 gene; PDCD10; TGCE; PROGRAMMED CELL-DEATH; ENCODING KRIT1; HETEROGENEITY; FAMILIES; ELECTROPHORESIS; EXPRESSION; ANGIOMAS; FEATURES; LINKAGE; PROTEIN